Improving Alluvial Soil Properties and Edamame (Glycine max L. Merr.) Growth Using Compost–Biochar - Agusalim Masulili; Rini Suryani; Sutikarini Sutikarini (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2026)
Edamame cultivation on alluvial soils in West Kalimantan faces persistent challenges related to poor soil quality, including low organic matter content, compacted structure, and limited nutrient retention capacity. This study evaluated the effectiveness of compost-biochar amendment to enhance soil properties and edamame growth on alluvial soil. A completely randomized design with 13 treatments in triplicates was employed, combining compost biochar doses (5, 10, and 15 ton/ha) with varying NPK fertilizer reduction levels (0%, 25%, 50%, and 75%). Compost consisted of water hyacinth compost and rice husk biochar mixed at 1:1 ratio (v/v), applied one week before planting. Results demonstrated significant improvements in both vegetative growth and soil chemical properties (p<0.05). The treatment combining 15 ton/ha compost with 25% NPK (C12) produced the highest number of branches (7.67) and trifoliate leaves (25.50), representing increases of 109% and 63% respectively over the control. Application of 10 ton/ha compost with 50% NPK reduction (C8) optimally enhanced soil organic carbon to 1.90% and water retention to 37.61%, demonstrating 46% and 7.2% improvements over untreated soil. These findings indicate that compost–biochar amendment can substantially improve soil quality while maintaining edamame growth under reduced NPK input. A reduction of up to 50% of NPK fertilizer is achievable without compromising soil improvement and plant performance, highlighting the potential of this approach for sustainable edamame production on alluvial soils.